The Impact of the Covid-19 Pandemic Process on Classroom Teacher Candidates' Self-Efficacy Beliefs in the Science Laboratory Applications Course - Nimet Akben (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Face-to-face instruction was discontinued due to the Covid-19 pandemic, and problems emerged with the implementation of the three-semester online and two-semester hybrid educational models, particularly in the courses that required laboratory studies. The science laboratory applications course, which the students of the classroom teaching program are responsible for, was one of the courses in which these difficulties were encountered. Within the scope of this course, pre-service teachers must conduct one-on-one experiments and present them to their peers. In this study, which attempted to determine the impacts of the practices that were not conducted during the pandemic process on the self-efficacy beliefs of teacher candidates for this course, first of all, the "Self-Efficacy Scale for the use of science laboratory" developed by Kızkapan and Saylan-Kırmizigul (2021) was used. The candidates' views regarding the various methods of conducting this course were then taken in writing. The analysis revealed that the candidates who took the course online and, in a hybrid learning environment had lower self-efficacy beliefs than the candidates who took the course face-to-face. Also, it was found that almost all of the pre-service teachers preferred to take the course face to face.